APPLICATION OF THE MIND MAPPING MODEL IN IMPROVING THE ABILITY OF WRITING EXPOSITION TEXTS IN CLASS X MIPA 4 STUDENTS OF SMA NEGERI 3 BANDA ACEH - Hendra Kasmi; Teuku Mahmud (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is entitled